2004
DOI: 10.2337/diacare.27.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Physician, Organizational, and Patient Factors Associated With Suboptimal Blood Pressure Management in Type 2 Diabetic Patients in Primary Care

Abstract: OBJECTIVE -To assess the quality of hypertension care in patients with type 2 diabetes in general practice and identify physician, organizational, and patient factors associated with suboptimal care.RESEARCH DESIGN AND METHODS -Data from 895 randomly selected diabetic patients were extracted from the electronic medical records of 95 general practitioners. Physician and organizational characteristics were collected with a questionnaire. We conducted a multilevel analysis to identify associations with blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 25 publications
5
26
0
2
Order By: Relevance
“…The findings of the present study regarding the quality of diabetes care in both general practice and outpatient clinic are in line with those of other studies performed in the Netherlands. [15][16][17][18] Consequently, the results of this study can be considered representative for the quality of diabetes care in the Netherlands.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The findings of the present study regarding the quality of diabetes care in both general practice and outpatient clinic are in line with those of other studies performed in the Netherlands. [15][16][17][18] Consequently, the results of this study can be considered representative for the quality of diabetes care in the Netherlands.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This may be attributed to workload and lack of resources to organize regular follow-up. 11,12 With the current model of health care, the attainment of these targets seem to be difficult in the majority of diabetic cases. Nurse-led clinics is an effective strategy in the intensification of BP monitoring and management for type II diabetics.…”
Section: Eyementioning
confidence: 99%
“…[2][3][4]25,26 Other studies reported superior diabetes control in larger practices. Our results correspond with other studies that suggest high-level recording of process measures but persisting suboptimal achievement of established intermediate outcome targets.…”
Section: E814mentioning
confidence: 99%